PERANCANGAN BUKU KATALOG BATIK LITUHDAYA INDONESIA MENGGUNAKAN TEKNIK FOTOGRAFI FASHION SEBAGAI UPAYA MENGENALKAN KEPADA MASYARAKAT SURABAYA - Bagus, Pratama Putra; Budiardjo, Hardman; cinantya, ixsora gempita (Jurnal Art Nouveau, 2017)
Batik is currently almost alienated and less desirable by the early adult because of the many fashion products that appear and with the current model. This is due to a lack of interest response to appreciate and preserve the original cultural heritage of Indonesia. Batik is one of the heritages that must be preserved, therefore the purpose of this research is to design the book catalog of Batik Lituhdaya Indonesia photography with fashion photography technique as an effort to introduce to surabaya society. Lituhdaya Indonesia is a batik fashion industry from Surabaya. In the  midst of a decline in interest  in batik and many fashion industries that have sprung up by offering a contemporary product, Lituhdaya Indonesia began to awaken batik fashion in early adult. From the results of data analysis, got Keyword Communication Messages "authentic" (something that has purity). The main concept can also be interpreted as the most prominent of its rivals, through the selection of designs that "authentic" pure batik expected to be better known and seeded than other products or other fashion industry is more popular today. Early adulthood disinterest of batik is caused by the lack of recognition to them and the batik  seems old-fashioned and outdated. Batik is also a culture that has a diversity depending on the region of origin. Currently batik has lost identity or less popular among early adults. The design of a photography for each batik from Lituhdaya Indonesia itself is expected to attract early adult interest in  cultural heritage, because the diusianya fairly mature, they will be more interested in things that are easily digested, such as fashion photos, photos of cuisine, photos of the environment and etc. Keywords: Photography Book, Batik, Fashion Photography, Cultural Heritage, Authentic